Digital Health Service Transformation in Enhancing Patient Care Quality in the Era of Society 5.0 - Lamria Situmeang; Iin Hardiyati; Nova Winda Setiati; Damon Wicaksi; Susanti Susanti (Mandalika Journal of Medical and Health Studies, 2025)
The rapid development of digital technology has significantly transformed healthcare systems, particularly in the era of Society 5.0, which emphasizes the integration of advanced technology and human-centered values. Digital health services, including electronic health records, telemedicine, artificial intelligence, and big data analytics, play a crucial role in enhancing patient care quality. This study aims to analyze the role of digital health service transformation in improving patient care quality and to identify strategic factors supporting its sustainable implementation. A qualitative approach using a literature review design was employed by analyzing scholarly articles, books, and official reports retrieved from reputable databases such as Scopus, PubMed, and Google Scholar. Data were analyzed through content and thematic analysis to identify major patterns and conceptual relationships. The results indicate that digital health transformation improves patient safety, diagnostic accuracy, service efficiency, accessibility, and patient-centered care. Furthermore, effective implementation is influenced by technological infrastructure, leadership commitment, digital literacy, data governance, and policy support. The study concludes that digital health transformation, when aligned with human values and ethical governance, serves as a strategic foundation for building high-quality, equitable, and sustainable healthcare systems in the Society 5.0 era.